Vertical integration, innovation, and alliance portfolio size: Implications for firm performance - Lahiri, Nandini; Narayanan, Sriram (Strategic Management Journal, 2013)
We examine the consequences of alliance portfolio configuration by focusing on contingencies that affect the impact of alliance portfolio size on innovation and financial performance. While increasing alliance portfolio size is expected to positively impact innovation and financial performance, we propose that, at high levels of innovation of the focal firm, increasing alliance portfolio size dampens financial performance. We also propose that firm boundaries moderate the impact of alliance portfolio size on innovation and financial performance differently. Specifically, vertically integrated firms benefit less (more) than their vertically specialized counterparts in leveraging higher innovation (financial) performance with increasing alliance portfolio size. Our analysis suggests that both vertical scope and innovation levels of the firm play an important role in understanding how alliance portfolios impact performance . Copyright © 2013 John Wiley & Sons, Ltd.